Mixed traffic flow in anisotropic continuum model - C. F. Tang (2018)
An extended speed gradient model is developed to study the mixed traffic flow of two types of vehicles with different velocities and different lengths. Two new terms, representing the reaction of one type of vehicle to the other, are proposed and built into the dynamic speed evolution equations for fast cars and slow vehicles. With the developed model, the relation between the steady-state behavior of the mixed traffic flow system and two system parameters is analyzed, including the number density ratio R of the fast cars to the total vehicles and the vehicle length ratio a of the slow vehicle to the fast car. The formation and propagation of traffic jams, the dissolution process of the jams, and the local cluster effect of the mixed traffic system are also studied. The simulation results are reasonable and consistent with daily experience.